<html><head><meta http-equiv="content-type" content="text/html; charset=utf-8"></head><body dir="auto"><div>You may have shown in a mathematics class that</div><div><br></div><div>1 + 2 + ... + &nbsp;n = n(n + 1)/2</div><div><br></div><div>Do you recall how you did it? What was the induction step?<br><br>Sent from my iPhone</div><div><br>On Sep 25, 2012, at 8:04 AM, Ashley Fowler &lt;<a href="mailto:afowler2@broncos.uncfsu.edu">afowler2@broncos.uncfsu.edu</a>&gt; wrote:<br><br></div><blockquote type="cite"><div>

<meta http-equiv="Content-Type" content="text/html; charset=iso-8859-1">



<div style="direction: ltr;font-family: Tahoma;color: #000000;font-size: 10pt;">I am trying to do a recursive analysis on the Sum of even numbers function. So far I have already defined the function. I have found the base case. The hard part is finding the
 non-recursive definition. I'm having trouble of what non-recursive definition even means.
<div><br>
</div>
<div>
<div>Step 1 - Base case: sumEven(N) = 2, if N = 1</div>
<div><br>
</div>
<div>Step 2 - Non-recursive definition =</div>
<div><br>
</div>
<div>(define sumEven</div>
<div>&nbsp; &nbsp; (lambda (N)</div>
<div>&nbsp; &nbsp; &nbsp; (cond((= N 1) 2)</div>
<div>&nbsp; &nbsp; &nbsp; &nbsp; &nbsp; &nbsp;((&gt; N 0) (*(+ N 1)N)))))</div>
</div>
</div>


</div></blockquote><blockquote type="cite"><div><span>____________________</span><br><span> &nbsp;Racket Users list:</span><br><span> &nbsp;<a href="http://lists.racket-lang.org/users">http://lists.racket-lang.org/users</a></span><br></div></blockquote></body></html>